Molecular Characterization of Mycobacterium avium subsp. hominissuis of Two Groups of Lymph Nodes, Being Intradermal Tuberculin or Interferon-Gamma Test Positive and Negative, Isolated from Swiss Cattle at Slaughter - Scherrer, Simone; Landolt, Patricia; Carroli, Natasha; Stephan, Roger (Frontiers in Veterinary Science, 2018)
Mycobacterium avium subsp. hominissuis (MAH) is an important zoonotic pathogen with raising global health concerns. In humans, MAH is one of the most widespread non-tuberculous mycobacterial species responsible for lung disease. In animals, MAH is frequently isolated from pigs; however, it is also an opportunistic pathogen for other mammals including cattle. To elucidate the genetic diversity of MAH in cattle, a molecular characterization of isolates (n = 26) derived from lymph nodes was performed. Fourteen isolates originated from slaughtered cattle with visible altered lymph nodes at meat inspection whereas twelve isolates were from lymph nodes without any gross pathological changes of healthy slaughtered cattle. Variable number of tandem repeat (VNTR) analysis was performed at 20 loci to examine genetic differences of isolates and to compare to previously reported VNTR data of human isolates from different countries. Genetic elements IS901, IS1245, IS1311, LSPA17, ITS1 sequevar and hsp65 code were determined. Interestingly, two bovine MAH isolates harbored ISMav6 and hsp65 code 15, which so far has only been observed in human isolates. We supposed that VNTR data of Swiss samples would show clustering with European samples. Minimum spanning tree and unweighted pair group method using arithmetic averages analyses based on the VNTR data indicated a specific cluster of MAH isolates obtained from lymph nodes without any gross pathological changes of healthy slaughtered cattle. Comparing Swiss isolates with isolates from different other countries no geographical clustering was observed; however, four Swiss isolates had an identical VNTR profile as human isolates from the Netherlands, USA and Japan. These findings indicate a possible public health issue.